Effects of Phosphorus and Zinc on Maize and Cowpea grown on Alfisols in Sourthern Nigeria - OSINAME, O.A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Trials were conducted at three locations on Alfisols in southwestern Nigeria to study the optimum phosphorus - zinc balance in the soil for field grown maize (Zea mays L) and cowpea (Vigna unguiculata s. sp. unguiculata L. Walp). The incidence of P induced Zn deficiency in maize was observed to be more probable in the sandy soils of the savanna zone than in the sandy loam soils of the forest zone. Correcting P deficiency without correcting Zn deficiency resulted in lower maize yields. In soils with Bray-1 P test of > 7.0 ppm and 0.1N HCL extractable Zn of < 1.0 ppm, further addition of P. was observed to induce Zn deficiency in maize. Cowpea was less sensitive to either the deficiencies of P and Zn or to the incidence of P induced Zn deficiency.